A Comparative Study of Hyperbaric Bupivacaine and Isobaric Ropivacaine for Spinal Anesthesia in Cesarean Section - Bohara, Chetan; Bhandari, Parshal; KC, Prabin; KC, Akanksha; Gyawali, Sakar; Bajracharya, Prashanna (Grande Medical Journal, 2025)
Background: Spinal anesthesia is preferred for cesarean section because of the onset and safety. Hyperbaric bupivacaine has long been the standard, whereas ropivacaine offers reduced cardiotoxicity and may provide better hemodynamic stability. This study compared intrathecal bupivacaine and ropivacaine in parturient undergoing elective cesarean section.Method: In this prospective cohort study, 84 patients received either 11 mg hyperbaric bupivacaine (Group B) or 11 mg isobaric ropivacaine (Group R). Sensory and motor block onset, duration of analgesia, hemodynamics, and adverse events were assessed.Result: Bupivacaine showed faster sensory block onset (2.43 vs 3.91 min), faster motor block onset (3.00 vs 3.79 min), and longer duration of analgesia (97.79 vs 82.86 min) (all p